2023
DOI: 10.1177/10711007231166667
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetic Evaluation of Hallux Valgus during Gait: A Systematic Review

Abstract: Background: Foot pathologies can affect the kinetic chain during gait, leading to altered loading at other joints that can lead to subsequent pathologies. Although hallux valgus is the most common foot disease, little has been discussed about the biokinetic effects of hallux valgus on the foot and lower limb. This systematic review evaluated the kinematic, kinetic, and pedobarographic changes of the hallux valgus foot compared to a healthy one. Methods: Several electronic databases were searched up to January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(224 reference statements)
0
1
0
Order By: Relevance
“…A recent systematic review consistently reported heterogeneity in definitions and normal values. 25 Our hypothesis is that there would be an increase in total foot contact time with aging possibly linked to a decrease in peak force at the heel level, caused by a loss of strength of muscles involved in the first 20% of the stance phase, 1 slowing of the center of force in the midfoot region, and delaying the arrival at the forefoot, losing propulsion in both sexes. A higher body mass index (BMI) could modify this situation.…”
Section: Introductionmentioning
confidence: 98%
“…A recent systematic review consistently reported heterogeneity in definitions and normal values. 25 Our hypothesis is that there would be an increase in total foot contact time with aging possibly linked to a decrease in peak force at the heel level, caused by a loss of strength of muscles involved in the first 20% of the stance phase, 1 slowing of the center of force in the midfoot region, and delaying the arrival at the forefoot, losing propulsion in both sexes. A higher body mass index (BMI) could modify this situation.…”
Section: Introductionmentioning
confidence: 98%